On Estimating the Survival Function for the Patients Suffer from the Lung Cancer Disease - Salman, Abbas N.; Farhan, Ibtehal H.; Ameen, Maymona M.; Hussein, Adel Abdulkadhim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In this paper, the survival function has been estimated for the patients with lung cancer using different parametric estimation methods depending on sample for completing real data which explain the period of survival for patients who were ill with the lung cancer based on the diagnosis of disease or the entire of patients in a hospital for a time of two years (starting with 2012 to the end of 2013). Comparisons between the mentioned estimation methods has been performed using statistical indicator mean squares error, concluding that the estimation of the survival function for the lung cancer by using pre-test singles stage shrinkage estimator method was the best   .